IMPLEMENTASI WEBSITE SEKOLAH UNTUK SMK IMTAQ DARURRAHIM SEBAGAI MEDIA INFORMASI DAN PENDAFTARAN SISWA BARU JAKARTA TIMUR - Yoga Sofyan Arief; Itca Bagus Setiawan; Roid Adip Akmal; Dadang Iskandar Mulyana (LPPM Institut Pendidikan Nusantara Global, 2025)
This Community Service activity aims to assist SMK Imtaq Darurrahim in developing a web-based information system to serve as a medium for disseminating school information and facilitating new student registration online. The system was designed and built using PHP with the CodeIgniter framework and MySQL as the database. The development process employed the Waterfall model, which includes the stages of requirement analysis, system design, implementation, testing, and maintenance. The system comprises three main modules: Information Media (announcements, news, gallery, and contact), Registration System (online registration form), and Management Dashboard (for content and registration data management by school staff). Implementation was carried out through training sessions for the admin and school staff to ensure independent system management. Black box testing showed that 96% of the system’s functions operated correctly, while 4% experienced minor bugs that were subsequently fixed. Server stability testing over a three-month period recorded a 99.8% uptime with an average response time of 1.2 seconds. Security testing identified one minor vulnerability, which was immediately resolved. Overall, the information system effectively meets the school's needs in delivering timely information and simplifying the online student registration process, with reliable performance and security.